2015
DOI: 10.1002/bab.1369
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl starch/alginate microspheres containing diamine oxidase for intestinal targeting

Abstract: The association of carboxymethyl starch (CMS) and alginate is proposed as a novel matrix for the entrapment of bioactive agents in microspheres affording their protection against gastrointestinal degradation. In this study, the enzyme diamine oxidase (DAO) from white pea (Lathyrus sativus) was immobilized by inclusion in microspheres formed by ionotropic gelation of CMS/alginate by complexation with Ca2+. The association of CMS to alginate generated a more compact structure presenting a lesser porosity, thus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 57 publications
1
23
0
1
Order By: Relevance
“…All polyanions used in the investigation have carboxyl groups [20,21]. e mixture of the different polyanions with the CS produced a hydrogel at a pH lower than 4, and the morphology of hydrogels is very sensitive to the preparation procedures [16,22,23]. In this study, differences which are related to the method used in each polymer gel were observed from SEM images.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…All polyanions used in the investigation have carboxyl groups [20,21]. e mixture of the different polyanions with the CS produced a hydrogel at a pH lower than 4, and the morphology of hydrogels is very sensitive to the preparation procedures [16,22,23]. In this study, differences which are related to the method used in each polymer gel were observed from SEM images.…”
Section: Resultsmentioning
confidence: 88%
“…In another study, Blemur et al [16] found that the ionotropic gelation of AA with CaCl 2 formed a porous structure, while chitosan interacted with alginate to form microspheres which exhibited porosity like alginate.…”
Section: Alginic Acid-(aa-) Based Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher catalytic capacity of DAO enzymes of plant origin in degrading certain amino substrates has been described by some authors in comparison with those of animal origin [ 129 , 135 , 136 , 137 ]. Specifically, the germinated sprouts of certain edible legumes have been pointed out as interesting sources of DAO enzyme.…”
Section: Histamine Intolerancementioning
confidence: 99%
“…Further studies are needed to evaluate the amounts of NH 3 released following the administration of DAO pills related to the amount generated by intestinal bacteria and that eliminated (intestinal absorption and by feces). This approach based on a vegetal DAO associated to Catalase is now in development and the bioactive enzymes will be formulated for oral administration as monolithic tablets conceived for lower intestine and colon delivery [66,67,74].…”
Section: Role Of Histamine In Enteric Dysfunctionsmentioning
confidence: 99%